2018
DOI: 10.3389/fonc.2017.00331
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA, an Antisense RNA, in Sensing Myeloid Malignancies

Abstract: Myeloid malignancies, including myelodysplastic syndromes and acute myeloid leukemia, are clonal diseases arising in hematopoietic stem or progenitor cells. In recent years, microRNA (miRNA) expression profiling studies have revealed close associations of miRNAs with cytogenetic and molecular subtypes of myeloid malignancies, as well as outcome and prognosis of patients. However, the roles of miRNA deregulation in the pathogenesis of myeloid malignancies and how they cooperate with protein-coding gene variants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 110 publications
(86 reference statements)
0
2
0
Order By: Relevance
“…MicroRNAs (miRs) are a classical non-coding small RNA playing crucial regulatory roles in diverse pathological and physiological progresses by a posttranscriptional mechanism through binding the 3 ′ -untranslated regions (3 ′ -UTR) of target genes (9)(10)(11)(12). And miRs can act as tumor oncogenes or suppressors through regulating their target genes that are usually dysregulated in cancer (13)(14)(15). In our current study, we have proven that miR-936 expression profile is meaningfully reduced in LSCC specimens, and overexpression of miR-936 suppresses LSCC cells proliferation migration and invasion.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRs) are a classical non-coding small RNA playing crucial regulatory roles in diverse pathological and physiological progresses by a posttranscriptional mechanism through binding the 3 ′ -untranslated regions (3 ′ -UTR) of target genes (9)(10)(11)(12). And miRs can act as tumor oncogenes or suppressors through regulating their target genes that are usually dysregulated in cancer (13)(14)(15). In our current study, we have proven that miR-936 expression profile is meaningfully reduced in LSCC specimens, and overexpression of miR-936 suppresses LSCC cells proliferation migration and invasion.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the cytogenetic aberrations observed in MDS, current studies have also revealed aberrant expression of microRNAs. 104 In MDS with deletion of the long arm of chromosome 5 [del(5q)] alleles of miR143, miR145, and miR146a are deleted within the commonly deleted region located on chromosome 5q32–5q33. 105 Lenalidomide therapy, indicated for this group of patients, leads to normalization of expression of these microRNA.…”
Section: Microrna Expression In Chronic Myelogenous Leukemiamentioning
confidence: 99%